2023
DOI: 10.1051/0004-6361/202244688
|View full text |Cite
|
Sign up to set email alerts
|

X-ray emission from a rapidly accreting narrow-line Seyfert 1 galaxy at z = 6.56

Abstract: Context. The space density of X-ray-luminous, blindly selected active galactic nuclei (AGN) traces the population of rapidly accreting super-massive black holes through cosmic time. It is encoded in the X-ray luminosity function, whose bright end remains poorly constrained in the first billion years after the Big Bang as X-ray surveys have thus far lacked the required cosmological volume. With the eROSITA Final Equatorial-Depth Survey (eFEDS), the largest contiguous and homogeneous X-ray survey to date, X-ray … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 149 publications
0
3
0
Order By: Relevance
“…These models are similar to the A19 curve, although slightly different in shape, and they lie well above our curve, particularly for z  2. The discrepancy between X-rays and theoretical simulations is known in the literature (e.g., Vito et al 2018;Barchiesi et al 2021;Wolf et al 2023), and it is generally explained with the challenges in efficiently detecting heavily obscured, Compton-thick sources in X-ray surveys (e.g., Hickox & Alexander 2018). These tensions suggest that Compton-thick AGNs may have a substantial role in the SMBHs accretion history, especially at high redshift, even though their contribution is still not well understood.…”
Section: Black Hole Accretion Densitymentioning
confidence: 99%
“…These models are similar to the A19 curve, although slightly different in shape, and they lie well above our curve, particularly for z  2. The discrepancy between X-rays and theoretical simulations is known in the literature (e.g., Vito et al 2018;Barchiesi et al 2021;Wolf et al 2023), and it is generally explained with the challenges in efficiently detecting heavily obscured, Compton-thick sources in X-ray surveys (e.g., Hickox & Alexander 2018). These tensions suggest that Compton-thick AGNs may have a substantial role in the SMBHs accretion history, especially at high redshift, even though their contribution is still not well understood.…”
Section: Black Hole Accretion Densitymentioning
confidence: 99%
“…2.2, the steep part of the X-ray spectrum of AGN with high accretion rates would need to be limited below the rest-frame 2 keV. However, the spectra of bright NLS1s are generally steeper than those of normal Seyferts at energies even above 2 keV, which is the case for the eROSITAdetected z ∼ 6.5 quasar HSC J0921+0007 (Wolf et al 2023), for example, which has Γ ∼ 3 in the rest-frame energies above ∼5 keV. This discrepancy needs to be further investigated using a larger sample such as that being gathered by the eROSITA All-Sky Survey (Merloni et al 2012;Predehl et al 2021).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…This means that, as well as objects similar to local NLS1s, more luminous counterparts at higher redshifts can also be detected in the eROSITA survey. An illustrative example has already been discovered: one of the Subaru high-z exploration of lowluminosity quasars (SHELLQs), HSC J0921+0007 at z = 6.56 (Matsuoka et al 2018), was detected by eROSITA and the subsequent Chandra observation revealed its steep spectrum of Γ 3.2 (Wolf et al 2023).…”
Section: Introductionmentioning
confidence: 99%